PENGARUH METODE PEMBELAJARAN BLENDED TERHADAP HASIL BELAJAR SISWA KELAS X BKP SMKN 1 LINTAU BUO MATA PELAJARAN GAMBAR TEKNIK - Rianto Tri Agusta; Nurhasan Syah (Jurnal Applied Science in Civil Engineering, 2021)
The background of this research is the result of the author's interviews with teachers who teach Engineering Drawing subjects at SMK N 1 Lintau, Department of DPIB and BKP as well as interviews with class X students of DPIB and BKP about learning carried out with face-to-face and online systems on Engineering Drawing subjects. The purpose of this study was to determine the effect of using Blended learning methods on student learning outcomes in Engineering Drawing subjects in the Construction and Property Business (BKP) class of SMK Negeri 1 Lintau Buo. This research uses experimental research with Non Equivalent Control Group design. This research design uses 2 classes, namely class X BKP rombel A as the experimental class and X BKP rombel B as the control class. The data obtained are the results of the students' pretest before being given the action and the posttest after the action is taken. Calculation of the hypothesis using the t-test obtained tcount of 1.182, where the value is smaller than ttable of 2.199 indicating that Ha is rejected and Ho is accepted. Thus it can be concluded that there is no significant effect on student learning outcomes using the Blended learning method on the subject of Engineering Drawing class X BKP at SMK N 1 Lintau.